2022
DOI: 10.1002/jcla.24757
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neutrophil gelatinase‐associated lipocalin predicted to contrast‐associated acute kidney injury after planned percutaneous coronary intervention in elderly patients

Abstract: Aim To determine the proportion of contrast‐associated acute kidney injury (CA‐AKI) after percutaneous coronary intervention (PCI) and the predictive value of urine neutrophil gelatinase‐associated lipocalin (uNGAL) for CA‐AKI in elderly patients with chronic coronary artery disease. Methods A total of 509 patients who had planned percutaneous coronary intervention (mean age was 63.58 ± 11.63 years and 63.3% of males) were divided into two groups: group 1 (n = 153; elderly patients) with ≥70 years old and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have shown that NGAL is an independent risk factor for AKI in elderly patients and can be used to evaluate the prognosis of DQ. 14,15 In this study, the blood NGAL levels of patients with AKI caused by DQ poisoning were significantly higher than those of healthy subjects on admission and increased with the aggravation of AKI, and the correlation analysis suggested that there was a positive correlation between the serum NGAL level and AKI grade. Furthermore, NGAL levels in the nonsurvival group were significantly higher than those in the survival group, suggesting that NGAL can determine the degree of organ function damage in patients and thus guide clinical treatment.…”
Section: Discussionmentioning
confidence: 52%
“…Recent studies have shown that NGAL is an independent risk factor for AKI in elderly patients and can be used to evaluate the prognosis of DQ. 14,15 In this study, the blood NGAL levels of patients with AKI caused by DQ poisoning were significantly higher than those of healthy subjects on admission and increased with the aggravation of AKI, and the correlation analysis suggested that there was a positive correlation between the serum NGAL level and AKI grade. Furthermore, NGAL levels in the nonsurvival group were significantly higher than those in the survival group, suggesting that NGAL can determine the degree of organ function damage in patients and thus guide clinical treatment.…”
Section: Discussionmentioning
confidence: 52%